Produção e caracterização de um anticorpo policlonal monoespecífico contra rNcp43 para o diagnóstico da neosporose - Sá, Gizele Lima de (2012)
Neosporosis is considered a disease of worldwide distribution. It is caused by the apicomplexa protozoan Neospora caninum, responsible for neuromuscular disorders in dogs and abortions in bovines, which makes it an important pathogen in cattle breeding. The diagnosis of this disease can be accomplished by identifying the parasites by histological sections or by detection of specific antibodies. However, serological methods can be hampered by cross-reactivity with other apicomplexa parasites, such as Toxoplasma gondii. Parasite-specific antigens used for detection of antibodies or in the production of antiserum for the detection of tachyzoites can improve the specificity and sensitivity of diagnostic tests and studies of the biology of the parasite. Among specific antigens of Neospora genus, NcSRS2 (Nc-p43) which is an immunodominant surface protein stands out. It is present in tachyzoites as well as bradyzoites. In this study, Nc-p43 protein was produced in its recombinant form (rNcp43), by inserting the gene NcSRS2 in the cloning vector pET100/DTOPO, which was used to transform Escherichia coli BL21 Star. rNc-p43 protein was evaluated for reactivity with immune sera from naturally infected bovine, ovine and canine species, and used to immunize BALB/c mice for the production of a polyclonal antibody (pAb). rNc-p43 (pAb/rNc-p43) antibody was conjugated to fluorescein isothiocyanate (FITC) and the reactivity with the native protein on the surface of the parasite was evaluated by immunofluorescence. rNc-p43 protein was recognized by anti N. caninum present in immune sera by ELISA and dot blot and it was able to generate antibodies against the p43 antigen. The pAb/rNc-p43 reacted with the rNc-p43 protein in indirect ELISA and Western blotting, detecting N. caninum tachyzoites in direct and indirect immunofluorescence, with a fluorescence pattern only in the apical complex of the parasite, maintaining affinity even after conjugation with FITC. pAb/rNc-p43 showed no cross-reactivity with T. gondii. The results of this study suggest that the rNc-p43 obtained and the pAb produced can be useful in developing diagnostic tests based on the detection of specific antibodies and the antigen present on the surface of the parasite.